The economic valuation of hawker culture in Singapore : a contingent valuation approach - Lee, Charles Jun Yu (Nanyang Technological University, 2020)
In an increasingly globalised world with rapid changes to our social and economic environment, Singapore faces many challenges preserving both its tangible and intangible heritage. In recent years, there has been growing recognition of Singapore’s unique hawker culture as being one of the most important aspects of the nation’s intangible cultural heritage. With the anticipation of challenges that hawker centres will increasingly face, such as manpower constraints and the relatively high median age (59 years old) of incumbent hawkers, Singapore government intends to allocate more resources to the preservation and promotion of Singapore’s hawker culture. In this project, we aim to estimate Singapore residents (local and permanent residents)’ willingness to pay for the preservation of Singapore’s hawker culture using the contingent valuation (CV) approach. This study would also estimate the total economic value of Singapore residents’ willingness-to-pay for Singapore’s hawker culture and ascertain which factors affect their WTP. In a demographically stratified sample of 400 Singapore residents (local and permanent residents), it is found that the average Singaporean’s WTP for Singapore’s hawker culture is S$38.2 a year, while the total economic value place on hawker culture in Singapore is S$97.2 million. An analysis of the Ordered Probit regression reveals that income, frequency of visits and the defining characteristics of hawker centres such as affordability of food and the convenience of being near one’s workplace or home have significant effect on WTP. It is of concern that the perceptions of community benefits, on the contrary, are not significant determinants of WTP of hawker culture. The results from this study would help better inform budget planning decisions for the government and ensure that the costs incurred to preserve hawker culture is worth its value.